Macroeconomic and Financial Policies for Climate Change Mitigation : A Review of the Literature - Krogstrup, Signe (IMF Working Papers; Working Paper ;, 2019)
Climate change is one of the greatest challenges of this century. Mitigation requires a large-scale transition to a low-carbon economy. This paper provides an overview of the rapidly growing literature on the role of macroeconomic and financial policy tools in enabling this transition. The literature provides a menu of policy tools for mitigation. A key conclusion is that fiscal tools are first in line and central, but can and may need to be complemented by financial and monetary policy instruments. Some tools and policies raise unanswered questions about policy tool assignment and mandates, which we describe. The literature is scarce, however, on the most effective policy mix and the role of mitigation tools and goals in the overall policy framework.